2014
DOI: 10.1083/jcb.201308028
|View full text |Cite
|
Sign up to set email alerts
|

Live imaging of prions reveals nascent PrPSc in cell-surface, raft-associated amyloid strings and webs

Abstract: PrPSc forms micrometer long amyloidic strings that can congregate in clusters and webs at the surface of living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 123 publications
(147 reference statements)
3
56
0
Order By: Relevance
“…9 In contrast, ovine PrP Sc -fibrils Sc in living cells which was observed by light, atomic force, and scanning electron microscopy to form thin, 5 mm-long structures on the cell surface. 36,37 Regarding the average width of PrP Sc -fibrils, their appearance in our AFM images was obscured by co-purified brain matter in the form of extraneous non-fibrillar material. Also the natural presence of GPI-anchor and un-, mono, and diglycosylated PrP Sc forms obscured the underlying proteinaceous parts of PrP Sc -fibrils causing high width standard deviations.…”
Section: Secondary and Ultrastructural Propertiesmentioning
confidence: 81%
“…9 In contrast, ovine PrP Sc -fibrils Sc in living cells which was observed by light, atomic force, and scanning electron microscopy to form thin, 5 mm-long structures on the cell surface. 36,37 Regarding the average width of PrP Sc -fibrils, their appearance in our AFM images was obscured by co-purified brain matter in the form of extraneous non-fibrillar material. Also the natural presence of GPI-anchor and un-, mono, and diglycosylated PrP Sc forms obscured the underlying proteinaceous parts of PrP Sc -fibrils causing high width standard deviations.…”
Section: Secondary and Ultrastructural Propertiesmentioning
confidence: 81%
“…Milk fat globule epidermal growth factor 8 (MFGE8) is a bifunctional secreted molecule that can bind to both phosphatidylserine on apoptotic cells and integrins on phagocytes, thereby bridging apoptotic bodies and phagocytes and facilitating phagocytosis (91). Because prion infectivity is usually associated with lipids (92,93), it is conceivable that MFGE8 is involved in prion clearance by microglia in prion-infected brains. Indeed, mice lacking MFGE8 (Mfge8 -/-) experienced augmented prion accumulation and accelerated disease progression after prion inoculation.…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…The work also provides for the first time experimental evidence to support the modeling study by Kuznetsov et al 23 which predicted that prion transfer through TNTs was more likely to occur via active transport of vesicles than through passive diffusion on the plasma membrane. Interestingly, Rouvinski et al 10 have shown PrP Sc strings on the surface of intercellular bridges between ScGT1 cells and shown that on the cell body they have a slow speed of diffusion (0-3 mm/5 min). We do not rule out the possibility that diffusion along the plasma membrane may also contribute to intercellular prion transfer through TNTs, however we have not observed this phenomenon in CAD cells.…”
Section: Prp C Levels Affect Tnt Formationmentioning
confidence: 99%
“…Because PrP is a GPI-anchored protein targeted to the outer leaflet of the plasma membrane we envision 2 possibilities by which PrP Sc could transfer though TNTs: by diffusion along the surface of the TNT, consistent with its localization to the plasma membrane or within the tube itself inside specific organelles or vesicles. A recent study reported that PrP Sc could form string-like aggregates on the plasma membrane surface, and the authors detect PrP Sc strings on intercellular bridges 10 thus suggesting that diffusion along the cell membrane surface might represent one method of transfer. On the other hand, numerous studies show that, in infected cells, a large percentage of PrP Sc is found internally, along the endocytic and secretory pathways.…”
Section: Introductionmentioning
confidence: 99%